Assessing the Knowledge, Attitude and Practices of Farmer on the Biology and Management of Chinese Citrus Fly in Bagmati Province of Nepal - Sharma, Sushmita; Tiwari, Sundar; Adhikari, Debraj; Gautam, Bhola (Journal of the Institute of Agriculture and Animal Science, 2023)
Chinese citrus fly is the major pest of sweet orange in citrus growing districts of Bagmati Province Nepal. Farmer’s production constrains and production problems such as Chinese citrus fly problem in sweet orange are not well documented and studied. This study was conducted in Sindhuli, Ramechhap, Dolakha and Kavre districts of Bagmati Province in 2021 with aim to understand the farmer’s perception, knowledge about CCF and their management practices using semi-structured questionnaire. Collected survey data was analyzed using the SPSS-20 and MS Excel. The survey results depicted that the intensity of Chinese citrus fly damage has been decreased in Sindhuli district with the infestation level of < 20% in sweet orange orchard. However, CCF population as well as their damage level was in increasing trend of > 50% in sweet orange orchard in Ramechhap, and > 80% in Dolakha and Kavre district. Chinese citrus fly loss has been recorded up to 25% in Mandarin orange in Dolakha and Kavre district. Maximum Chinese citrus fly loss was recorded in sweet orange orchard in October month. Farmers usefully managed the dropping fruits by collecting in plastic bags and burying in pits. Great fruit fly bait, has been used for the CCF management in three districts except in Kavre. Majority of farmers reported that chemical pesticides are less effective or sometime not-effective for this pest management. This study provides a preliminary information about sweet orange orchard management practices, general pest problems, Chinese citrus fly and future management strategy in survey districts.